STRATEGI KOMUNIKASI DINAS PARIWISATA DAN KEBUDAYAAN DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN MAMUJU - Masyhadiah Masyhadiah (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to investigate the communication strategy of the Department of Tourism and Culture in developing and promoting tourism in Mamuju Regency, as well as to find out the impact of communication strategies. This study uses a mixed method of sequential exploration design which means producing descriptive data related to tourism development in Mamuju Regency. Data is collected through observation, interviews and documentation. Data were analyzed using Miles and Huberman analysis, SWOT analysis, and frequency tables. The results showed that in the framework of developing tourism, the Office of Tourism and Culture had sought to provide tourism infrastructure and facilities at each tourist site, partnering with the private sector, empowering local residents by forming tourism awareness groups, and Mamuju community youth. Promotions are also used such as public relations or publicity, special events and experiences, and direct marketing.